Electromechanics of planar HASEL actuators. (October 2021) - Kirkman, Sophie; Rothemund, Philipp; Acome, Eric; Keplinger, Christoph
Abstract: Soft actuators promise to expand the capabilities of conventional robots, allowing them to navigate unstructured terrain and to safely interact with humans. HASEL (hydraulically amplified, self-healing, electrostatic) actuators are a class of soft actuators that feature direct electrical activation via Maxwell stress, electrical self-healing, and fast actuation. Planar HASEL actuators, a subset of HASELs that expand in-plane upon activation, comprise a stretchable dielectric shell that is coated with compliant electrodes and filled with a liquid dielectric. While planar HASEL actuators have demonstrated strong experimental performance, the details of the underlying electromechanics are yet to be explored. In experiments, two mechanisms of deformation are observed: elastic stretching and electrohydraulic "zipping". This letter analyzes these mechanisms using two examples: a circular planar HASEL actuator that stretches equibiaxially, and a linear actuator that both stretches and zips. We use an energy minimization approach to derive nonlinear electromechanical models for their quasistatic actuation behavior. The analysis shows that the actuation behavior of circular HASEL actuators is similar to that of dielectric elastomer actuators (DEAs), and reveals how the added liquid layer in planar HASELs reduces their stiffness, allowing them to achieve greater strains than DEAs of the same dimensions. For the linear actuator, the model displays how the actuator only stretches until it reaches a critical voltage at which it starts to zip, drastically increasing strain. This work lays the foundation for the theoretical analysis of planar HASEL actuators, which consist of stretchable materials.